Implications of Kappa Suprathermal Halo of the Solar Wind Electrons - Pierrard, Viviane; Lazar, Marian; Stverak, Stepan (Frontiers in Astronomy and Space Sciences, 2022)
The electron velocity distributions measured in-situ in space plasmas reveal two central populations, a low-energy and highly dense (quasi-)thermal core, and a more diffuse but hotter suprathermal halo. Even if the core contributes much more to the total number density than the suprathermal particles, the energetic electrons play an important role in the higher moments. Using a dataset of more than 120000 solar wind observations of electron distributions, measured in the ecliptic between 0.35 to 3.3 AU, we investigate here the main characteristics of the halo population and its potential influence on the core, and macroscopic properties of electrons, i.e., number density (n), bulk velocity (u), temperature (T) and temperature anisotropy. The analysis indicates that the parameters exhibit interdependence trends characterized by correlations between certain of these parameters and the kappa exponent corresponding to the power law of the halo population tail. The links between low kappa and low number densities (of both the core and halo populations) confirm that Coulomb collisions can be quite ineffective even at low radial distances if the density of the plasma is sufficiently low. Moreover, halo populations with lower values of  are also associated to higher temperature anisotropies, and to higher bulk velocity. An interdependence between core and halo populations is also suggested by an apparent (inverse) correlation between their density and temperature ratios. We further show relations between the parameters fitting the sum of a Maxwellian core and a Kappa halo, and those of a global (single) Kappa fit that incorporates both the core and halo components. Such a global Kappa is used in an exospheric model of the solar wind, to predict the influence of suprathermal electrons on the characteristics of the solar wind. These results should stimulate future detailed analysis of these relationships and correlations, which may contribute to a realistic modeling of the solar wind and the formation and evolution of suprathermal populations.